Numerical study of rainstorm influence on parachute airdropping based on the smoothed particle hydrodynamics/arbitrary Lagrangian–Eulerian coupling method. (April 2020) - Yan, Linbo; Sun, Zhengkai; Cheng, Han
In order to study the influence of rainstorm on parachute dropping, the smoothed particle hydrodynamics/arbitrary Lagrangian–Eulerian coupling method is proposed. Finite elements are used to describe the continuous material such as fabric and air flow field, and the smoothed particle hydrodynamics particles are used to describe the discrete raindrops. The coupling between different fluid and structure is realized by penalty function. In order to distinguish the most influential factor of rainstorm environment on parachute, the effects of raindrop field and wind field in rainstorm are studied, respectively. It could be found that the raindrop fields with different droplet sizes have little effect on the parachute's shape, opening shock, and performance according to the comparative analysis, while the vertical wind field has a great influence on parachute's deceleration performance. The wind field, not the raindrop field, is the most important factor affecting the parachute's deceleration performance. The method and conclusions in this article could provide some references for parachute design.